Understanding Industry 4.0: Definitions and insights from a cognitive map analysis - Benitez, Guilherme Brittes (2019)
Goal: The purpose of this paper is to present an analysis of Industry 4.0 concepts and technologies through the lens of practitioners and scholars with considerable expertise in this field. Design / Methodology / Approach: A qualitative research was conducted based on seven semi-structured interviews guided by an open questionnaire, which was developed with the main goal of understanding the concept of Industry 4.0 and the technologies that compose this industrial phenomenon. Results: Based on this methodology, a cognitive map is presented as the result and final product of this study. This cognitive map is composed of five different clusters, each one represented by different colors, which relate to each of the questions in the questionnaire. Our analysis provides a better understanding of (i) the main concepts of Industry 4.0; (ii) the implementation stages for companies; (iii) the main enabling technologies; (iv) the concept of M2M (machine-to-machine); and (v) the scenario in Brazil. Each one of the clusters enables a discussion by bringing what is in the literature on the topic. Limitations of the investigation: The main limitations of the article are found in the subjectivity of the results and also in the scarcity in the literature related to some topics covered in the clusters. Practical implications: This research can be potentially useful for practitioners, since it sheds light on the Industry 4.0 concept and how technologies are used to integrate processes. Originality / Value: The clusters answers of the cognitive map allowed comparisons with the literature and a discussion about Industry 4.0, making it possible to direct and check gaps in the research.